After dark : the nocturnal urban landscape and lightscape of ancient cities - Gonlin, Nancy; Strong, Meghan E. (University Press of Colorado, 2022)
"After Dark explores the experience of nighttime within ancient urban settings. Contributors present evidence related to how ancient people manipulated and confronted darkness and night in urban landscapes, advancing our knowledge of the archaeology of cities, the archaeology of darkness and night, and lychnology (the study of ancient lighting devices)"-- Provided by publisher.
Keywords: Cities and towns, Ancient.; Municipal lighting -- History.; City and town life -- History.; Lighting -- Social aspects.; Night -- Social aspects.; Sociology, Urban.; Villes antiques.; Éclairage public -- Histoire.; Vie urbaine -- Histoire.; Nuit -- Aspect social.; Sociologie urbaine.; urban sociology.; SOCIAL SCIENCE / Archaeology.; SOCIAL SCIENCE / General; Cities and towns, Ancient; City and town life; Lighting -- Social aspects; Municipal lighting; Night -- Social aspects; Sociology, Urban; Electronic books.; History